2015
DOI: 10.1089/jop.2014.0005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intracameral Injection of Ranibizumab and Bevacizumab on the Corneal Endothelium by Scanning Electron Microscopy

Abstract: The SEM examination pointed out deterioration in endothelial cell morphology after intracameral injection of 1 and 0.5 mg ranizumab. However, the effects of intracameral bevacizumab injection on corneal endothelial cells were similar to those found in fellow eyes and the control group. Further large-scale studies that examine the cellular changes by transmission electron microscopy are required to support the results of the present study that evaluates the structural changes in endothelial cells by SEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…Fakat, literatürde bildirilen çalışmalarda, intravitreal ranibizumab, bevacizumab ve pegaptanib uygulamalarının endotel üzerine toksik etkilerinin olmadığı gösterilmiştir. 8,9 Mevcut literatürde, diyabetli hastalarda makuler ödem tedavisi için uygulanan intravitreal aflibercept enjeksiyonunun kornea endoteline ve ön kamaraya etkisini değerlendiren bir çalışma yoktur.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Fakat, literatürde bildirilen çalışmalarda, intravitreal ranibizumab, bevacizumab ve pegaptanib uygulamalarının endotel üzerine toksik etkilerinin olmadığı gösterilmiştir. 8,9 Mevcut literatürde, diyabetli hastalarda makuler ödem tedavisi için uygulanan intravitreal aflibercept enjeksiyonunun kornea endoteline ve ön kamaraya etkisini değerlendiren bir çalışma yoktur.…”
Section: Discussionunclassified
“…tarafından, daha yüksek ön kamara konsantrasyonlarının oluştuğu ön kamaraya uygulanan anti-VEBF enjeksiyonlarında dahi tavşan kornea endotelinde toksik etkinin olmadığı bildirilmiştir. 9 VEBF'nin ve reseptörlerinin kornea gibi avasküler bir yapının fizyolojisinde nasıl bir rol oynadığı tam olarak aydınlatılamamıştır. Ambati ve ark., korneada bulunan VEBF'nin neredeyse tamamının sflt-1 isimli bir protein tarafından inaktive edildiğini ve sadece korneal yaralanma ya da inflamasyon durumunda VEBF'nin aktif forma dönebildiğini bildirmişlerdir.…”
Section: Discussionunclassified
“…Burighel, Caicci, and Manni () reported similar structures in scanning electron micrographs of the coronal organ of an adult ascidian to be apical extensions of the membranes of supporting cells. A number of other studies have included micrographs that show similar structures on the ascidian coronal organ (Caicci, Burighel, & Manni, ; Caicci et al, ; Manni, Mackie, Caicci, Zaniolo, & Burighel, ) and on the cornea of rabbits (Ari et al, ). Examination by transmission electron microscopy is needed to reveal the relationship of these structures in urns to the junctional complex of urns reported by Jans and Jangoux ().…”
Section: Discussionmentioning
confidence: 99%
“…Rabbits have been widely used as an experimental model for ophthalmic research (ATILLA et al, 2003;MENCUCCI et al, 2005;ARI et al, 2015). The goal of the present study was to evaluate the cell density and percentage of hexagonal cells because these are the most reliable parameters for evaluating the integrity of the corneal endothelium (ABIB & BARRETO, 2001;PIGATTO et al, 2006;NAGATSUYU et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that rabbit corneal endothelium repairs by cell division and Brambatti et al migration (MORITA, 1995). Rabbits have been widely employed in the evaluation of the effects of surgical procedures and drugs on the corneal endothelium (ATILLA et al, 2003;MENCUCCI et al, 2005;ARI et al, 2015). However, there are few published references regarding endothelial density in rabbits.…”
Section: Introductionmentioning
confidence: 99%